2022
DOI: 10.1017/s0263574722000303
|View full text |Cite
|
Sign up to set email alerts
|

FAT-based robust adaptive controller design for electrically direct-driven robots using Phillips q-Bernstein operators

Abstract: This article proposes a robust and adaptive controller for industrial robot arms with multiple degrees of freedom without the need for velocity measurement. Many of the controllers designed for manipulators are model-based and require detailed knowledge of the system model. In contrast to these methods, this paper proposes a model-free controller using the Philips q-Bernstein operator as universal approximator. The designed controller can approximate uncertainties including external disturbances and unmodeled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Industrial robots based on trajectory planning algorithms and kinematics account for more than 20% of the high-end electronics market and are mainly used for welding, processing, assembly, sorting, and cleaning of electronics. 6 The application levels of various trajectory planning algorithms in industrial robots at home and abroad are shown in Figure 7.…”
Section: Figure 5 Trajectory Planning Algorithmmentioning
confidence: 99%
“…Industrial robots based on trajectory planning algorithms and kinematics account for more than 20% of the high-end electronics market and are mainly used for welding, processing, assembly, sorting, and cleaning of electronics. 6 The application levels of various trajectory planning algorithms in industrial robots at home and abroad are shown in Figure 7.…”
Section: Figure 5 Trajectory Planning Algorithmmentioning
confidence: 99%
“…23,24 The considerable point is that, despite the universal approximation feature of the neural networks/fuzzy systems to approximate nonlinear functions; they experience restrictions, turning their construction and design into a complex issue. 25,26 In approximators based on fuzzy logic, several parameters such as numerical ranges/types of membership functions, the inference system, fuzzification/defuzzification approaches, and the rule database must be selected appropriately to accomplish the design goals. On the other hand, in approximators based on neural networks, features such as the number of neurons/hidden layers, the network architecture, and the activation functions' type should be properly chosen.…”
Section: Introductionmentioning
confidence: 99%
“…While fuzzy systems and neural networks may estimate multiple functions based on their universal approximation characteristic, they suffer limitations that turn their design and construction into complex problems (Izadbakhsh et al, 2021d; Deylami and Izadbakhsh, 2021a; Izadbakhsh et al, 2022a). In fuzzy logic-based approximators, various parameters such as types and numerical ranges of membership functions, methods of fuzzification/defuzzification, the inference system, and the rule database should be chosen properly to fulfill the design objectives.…”
Section: Introductionmentioning
confidence: 99%